2019
DOI: 10.1177/0972150919862660
|View full text |Cite
|
Sign up to set email alerts
|

Green Advertising: Examining the Role of Celebrity’s Credibility Using SEM Approach

Abstract: Amid rising concern about protecting environment and reducing carbon emission, marketers do not just need to advertise their product to inform and persuade the consumers, rather they are required to convince the consumers that their product is environment friendly and do not cause any harm to the environment. Celebrity Advertising has been very popular among the marketers, as these celebrities help to generate favourable attention towards the product. While choosing an endorser/celebrity, his/her credibility p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 69 publications
2
34
1
3
Order By: Relevance
“…The prior scholars confirmed that celebrities could influence green buying behavior (Kumar & Tripathi, 2019). Industries are growing with time, along with that the sales of goods and services also shooting up, but when we see their impact on the environment, it is getting worse.…”
Section: Celebrity Endorsement and Green Consumer Buying Behaviormentioning
confidence: 99%
“…The prior scholars confirmed that celebrities could influence green buying behavior (Kumar & Tripathi, 2019). Industries are growing with time, along with that the sales of goods and services also shooting up, but when we see their impact on the environment, it is getting worse.…”
Section: Celebrity Endorsement and Green Consumer Buying Behaviormentioning
confidence: 99%
“…They, therefore, subsequently influence the attitudes of consumers as well as their respective intentions and perceptions. With the above, the study will add to the small body of research in the non-tourism field involving celebrity participation in green ads from other aspects (Dutta & Singh, 2013;Eren-Erdogmus, Lak & Çiçek, 2016;Kumar & Tripathi, 2019). The findings from this study may give insight towards the implementation of celebrity endorsement in green ads in the context of a broader contemporary marketplace.…”
Section: Introductionmentioning
confidence: 78%
“…As for the Source Credibility Theory, the value of the message in a particular ad is determined momentously by the level of expertise and trustworthiness displayed by the celebrity (Kumar & Tripathi, 2019). Trustworthiness is described as the level of honesty, dependability, believability and level of confidence of a celebrity in the endorser (Jolly, 2016).…”
Section: Celebrity Endorsement and Millennials' Behavioural Intentionsmentioning
confidence: 99%
“…Purchase intention (PI) is defined as the possibility of an individual to purchase a product/brand and has a strong link between perceptions and attitudes of consumers [41]: that is to say, they can change their decisions influenced by price, quality, and perceived value [42]. In the green-marketing context, when a consumer has purchase intentions by a specific green product or service, it is possible to talk about green consumption.…”
Section: Hypothesis 12 Brand Credibility Positively Affects Purchase Intentionmentioning
confidence: 99%